Glycoscience: Biology and Medicine - Taniguchi, Naoyuki; Endo, Tamao; Hart, Gerald W.; Seeberger, Peter H.; Wong, Chi-Huey (SpringerLink Bücher, 2015)
The aim of the book is to provide a succinct overview of the current status of glycoscience from both basic biological and medical points of view and to propose future directions, in order to facilitate further integrations of glycoscience with other fields in biological and medical studies. Glycans (carbohydrate oligomers) are the so-called “building blocks” of carbohydrates, nucleic acids, proteins and lipids and play major roles in many biological phenomena as well as in various pathophysiological processes. However, this area of glycoscience has been neglected from the research community because glycan structures are very complex and functionally diverse and as compared to proteins and nucleic acids simple tools for the amplification, sequencing and auto-synthesis of glycans are not available. Many scientists in other fields of research have now realized that glycosylation, i.e. the addition of glycans to a protein backbone, is the most abundant post translational modification reactions and is an important field of research and sometimes they require a glycobiology and/or glycochemistry approach to be used. It is still difficult, however, for non-expert researchers to use these techniques. This book provides numerous but simple overviews of current topics and protocols for the experiments. The book is aimed at university students and above, including non-experts in the field of glycoscience